Disparities in Access to Educational Media and Child Labor - Crosta, Facundo Luis (Education Policy Analysis Archives, 2007)
This paper presents an innovative way of analyzing the effects of child labor on the access to the educational system. The results show that an integrated analysis of achievement in the educational system allows for a more precise identification of the heterogeneities involved in access to such system. To this end, an index of orderly categories is built, allowing us to show some of the different ways that the relation of individuals with the system can take. The analysis is based on microdata withdrawn from the ECV 2001 for Argentina. It is shown that child work is a significant variable to explain why some individuals are not at grade level corresponding to their age. What?s more, the interactions between occupation and age, gender, and poverty reveal that this effect increases for males 15 years or older and poor. It is shown that observable individual characteristics such as age and sex are the ones that establish differences in access to the educational system, thus becoming relevant instruments for public policy. Besides, this result suggests that policy that allots the same amount of money to all secondary school students without considering age and gender does not seem to be the best answer to solve the problem of academic achievement at this level. A more in-depth study is necessary to be able to evaluate the simultaneity of decisions about work and study and their relationship with the availability of financial resources at home.